Structure and agency: understanding water policy changes in West Africa - Cherlet, Jan; Venot, Jean-Philippe (IWA Publishing, 2013)
Ownership of development processes has been high on the international agenda since the Paris Declaration of 2005. There is, however, much discussion about whether highly aid-dependent governments can really ‘own’ policy reforms in their countries. In this paper, we argue that the ownership of policy reforms is the outcome of an interaction between individual agency and structural conditions. Taking the implementation of Integrated Water Resources Management (IWRM) in Burkina Faso (since 1996) and Mali (since 2004) as an entry point, the paper describes the interplay between national policy makers, international organizations and dominant development discourses in the shaping of water policy reforms in both countries over the past 15 years. Despite the apparent uniformity of the global IWRM paradigm, a qualitative comparison of water policy changes in the two countries shows that policy reforms, as well as the extent to which they are ‘owned’ by national policy makers, are significantly distinct. This can be explained by different forms of individual agency and diverse structural conditions at a national level.